2016
DOI: 10.1016/j.jss.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer sphingosine-1-phosphate is associated with phospho-sphingosine kinase 1 and lymphatic metastasis

Abstract: Background Sphingosine-1-phosphate (S1P), a pleiotropic bioactive lipid mediator, has been implicated as a key regulatory molecule in cancer through its ability to promote cell proliferation, migration, angiogenesis and lymphangiogenesis. Previous studies suggested that S1P produced by sphingosine kinase 1 (SphK1) in breast cancer plays important roles in progression of disease and metastasis. However, the associations between S1P and clinical parameters in human breast cancer have not been well investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 47 publications
11
63
0
Order By: Relevance
“…We previously demonstrated that SphK1, but not SphK2, produces S1P that is exported from MCF7 breast cancer cells stimulated by estradiol (10). We also demonstrated that expression of SphK1 is upregulated in human breast cancers (11) and the level of activated, phosphorylated SphK1 correlates with lymphatic metastasis (12), in agreement with reports by others (13,14). …”
Section: Introductionsupporting
confidence: 92%
“…We previously demonstrated that SphK1, but not SphK2, produces S1P that is exported from MCF7 breast cancer cells stimulated by estradiol (10). We also demonstrated that expression of SphK1 is upregulated in human breast cancers (11) and the level of activated, phosphorylated SphK1 correlates with lymphatic metastasis (12), in agreement with reports by others (13,14). …”
Section: Introductionsupporting
confidence: 92%
“…Another study to analyze sphingolipid level in tumor tissue of breast patients and demonstrated high expression of pSPHK1 is associated with higher levels of S1P, which in term is associated with lymphatic metastasis in breast cancer 47. Some references providing clinical evidence to show the S1P axis involved in the therapies resistant of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that S1P is strongly associated with lymphatic network development [7, 8] and lymphatic metastasis in cancer patients [9, 10, 11]. Further, we have shown that S1P links inflammation and cancer in colitis-associated colon cancer [12, 13].…”
Section: Introductionmentioning
confidence: 93%